1988
DOI: 10.1002/ijc.2910410221
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization and oncogene expression in human colorectal carcinoma cell lines

Abstract: To establish well-characterized cellular reagents for the study of colon carcinoma, we have examined 19 human colorectal carcinoma cell lines with regard to morphology, ultrastructure, expression of tumor-associated antigens, proliferative capacity in vitro, anchorage-independent growth, oncogene expression, tumorigenicity and malignant potential. Cell lines examined were cultured under identical conditions, and in vitro and in vivo analyses were performed in parallel on replicate cultures. Three classes of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
3
4

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(114 citation statements)
references
References 52 publications
6
99
3
4
Order By: Relevance
“…Data associating c-myb gene ampli®cation with colon carcinomas and adenomatous polyps has been con¯icting (Yokata et al, 1986;Meltzer et al, 1987;Torelli et al, 1987;Grego et al, 1994). However, studies examining colon tumour cell lines have consistently reported a very low incidence of c-myb gene ampli®cation (Alitalo et al, 1984;Melani et al, 1991;Trainer et al, 1988). The data presented in this study supports these ®ndings as there was no evidence of ampli®cation in any of the seven human colon tumour cell lines examined.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Data associating c-myb gene ampli®cation with colon carcinomas and adenomatous polyps has been con¯icting (Yokata et al, 1986;Meltzer et al, 1987;Torelli et al, 1987;Grego et al, 1994). However, studies examining colon tumour cell lines have consistently reported a very low incidence of c-myb gene ampli®cation (Alitalo et al, 1984;Melani et al, 1991;Trainer et al, 1988). The data presented in this study supports these ®ndings as there was no evidence of ampli®cation in any of the seven human colon tumour cell lines examined.…”
Section: Discussionsupporting
confidence: 80%
“…In the colonic system, c-myb expression is observed in normal murine and human colonic mucosa and is present at elevated levels in human pre-malignant adenomatous polyps, tumours and tumour cell lines (Alitalo et al, 1984;Torelli et al, 1987;Trainer et al, 1988;Ramsay et al, 1992;Thompson and Ramsay, 1995). In contrast to c-myb expression in transformed hemopoietic tissues and cells of murine and avian origin, there was no evidence of Myb protein truncation (Ramsay et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Tumorigenicity has been tested by ATCC and is detailed on their website (www.atcc.org) and in Quinn et al, (1979) and Trainer et al, (1988).…”
Section: Cells Lines and Culturementioning
confidence: 99%
“…Moreover, many previous publications have utilized the soft agar assay to demonstrate the transformation capacity of oncogenes (Rasmussen et al, 2001;Lu et al, 2008;Syed et al, 2008;Monsel et al, 2010), as this assay is well documented to be predictive of in vivo tumorigenicity (Rhim, 1983;Trainer et al, 1988), malignant potential (Montesano et al, 1977) and drug response (Zirvi et al, 1983;Scholz et al, 1990). Taken together, these observations increase confidence in the oncogenic potential of the miR-506-514 cluster.…”
mentioning
confidence: 92%